Students’ motivation to study dentistry in Malaysia - Che Musa, Muhd Firdaus; Gallagher, Jennifer E.; Bernabe, Eduardo (2014)
Malaysia has extended their dental workforce in order to meet the growing populations, oral health needs and demands. Given this, it is vital to explore the view of students in order to inform workforce planning in Malaysia. Objectives To explore students’ motivation to study dentistry as a professional career and whether it varies by students’ socio-demographic characteristics. Method This study uses data from a questionnaire survey of all 530 final year dental students in the 11 dental schools (6 public and 5 private) in Malaysia. The self-administered questionnaire, developed at King’s College London [1], was adapted for the Malaysian context; has six sections including one on motivation to study dentistry and another on demographic characteristics (age, sex, ethnicity, family income and school type), which were used for this analysis. Responses on motivation to study dentistry were collated using 5-point Likert scales. Confirmatory factor analysis (CFA) was used to test six-factor structural model for career motivation, namely personal-background (F1), career’s advising (F2), academic/skills (F3), economy (F4), public service (F5) and features of the job (F6). Multivariate analysis of covariance (MANCOVA) was then used to compare the six factor scores by participants’ socio-demographic characteristics. Results Eight schools agreed to participate in the survey (all public and 2 private). Of the 431 final year students in those schools, 356 completed the questionnaire (67% of the full population) and 330 with complete data were included in this analysis. The majority were aged 24 years (47%), female (70%), Malay (56%), from middle-income families (41%) and public schools (78%). CFA showed that a six-factor model was a good characterisation of students’ motivation to study dentistry (Chi square: 789.3; degrees of freedom: 215; p<0.001; RMSEA: 0.087; CFI/TLI: 0.92). F6 and F1 were the strongest and weakest motivations (standardised factor loadings: 0.84 and 0.55 respectively). MANCOVA showed significant differences in factor scores for F2, F3 and F6 by sex, F4 by school type and F5 by ethnicity. No differences were found by age or family income. Conclusion ‘Features of the job’ were the main motivation to study dentistry among these students. There were some variations in motivation by sex, ethnicity and type of school, but not by age or family income.